Surface Characteristics and Catalytic Oxidation of CO on Silicalites and Silicalites Containing Cobalt, Copper and Silver Oxides - Farid Sh. Mohamed (Adsorption Science & Technology)
Two silicalite samples, S 1 and S 2 , were prepared hydrothermally in the presence of tetrapropylammonium bromide (TPA–Br) and tetrabutylammonium bromide (TBA–Br), respectively. Cobalt oxide, copper oxide or silver oxide (all at 10 wt% concentration) were incorporated into the S 1 and S 2 silicalites by impregnation methods. The structural and textural properties of the prepared samples were studied using a variety of techniques together with their ability to catalyze the oxidation of CO. The results obtained indicated that S 1 and S 2 existed as pure phases with structures analogous to those of ZSM-5 and ZSM-11 zeolites, respectively. Electron microscopic analysis showed that the crystalline morphology of S 1 and S 2 consisted of intergrown discs and shelf-like shapes with diameters in the range 10–15 μm and 29–33 μm, respectively. Differences noted during kinetic studies of CO oxidation over the prepared samples were discussed.